2018
DOI: 10.1103/physrevb.98.014507
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and field dependence of the intrinsic tunnelling structure in overdoped Bi2Sr2CaCu2O8+δ

Abstract: We report intrinsic tunneling data for mesa structures fabricated on three over-and optimally-doped Bi 2.15 Sr 1.85 CaCu 2 O 8+δ crystals with transition temperatures of 86-78 K and 0.16-0.19 holes per CuO 2 unit, for a wide range of temperature (T) and applied magnetic field (H), primarily focusing on one overdoped crystal (OD80). The differential conductance above the gap edge shows a clear dip structure which is highly suggestive of strong coupling to a narrow boson mode. Data below the gap edge suggest tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The inset to (b) shows that the minimum value increases as T c (estimated from the peak in specific heat) goes to zero. As found previously 66 , near T c the pair-breaking scattering rate diverges, reflecting superconducting fluctuations, and is responsible for the gap-filling behaviour observed in ARPES [31][32][33] , tunneling [34][35][36] and Raman 37,38 spectroscopies.…”
Section: Specific Heatsupporting
confidence: 72%
See 1 more Smart Citation
“…The inset to (b) shows that the minimum value increases as T c (estimated from the peak in specific heat) goes to zero. As found previously 66 , near T c the pair-breaking scattering rate diverges, reflecting superconducting fluctuations, and is responsible for the gap-filling behaviour observed in ARPES [31][32][33] , tunneling [34][35][36] and Raman 37,38 spectroscopies.…”
Section: Specific Heatsupporting
confidence: 72%
“…This is evidenced by specific heat [18][19][20][21][22] , NMR 23 , magnetic penetration depth [24][25][26][27][28][29] and THz spectroscopy 30 measurements. ii) The jump in specific heat at T c and the superfluid density at T = 0 decrease towards zero (a consequence of i)) iii) As temperature increases to T c , angle-resolved photoemission spectroscopy (ARPES) [31][32][33] , tunneling [34][35][36] and Raman spectroscopy 37,38 experiments have revealed that the superconducting gap fills-in rather than closes. This is at odds with BCS theory 39 , even though the ratio of the gap magnitude to T c is close to the d-wave weak-coupling BCS value 22,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows plotted as a function of for T = 6, 8, 10, 12 and 14 K. Above 1 tesla the behaviour is linear, consistent with the expected phenomenology of the Volovik effect. Such behaviour has been seen in the specific heats of single-crystal Y123 28 and 29 , and in interlayer tunneling in Bi2212 30 . For d -wave symmetry, in the superconducting state the finite ground-state specific heat coefficient is 29 in units of mJ/g.at.…”
Section: Volovik Effectmentioning
confidence: 78%
“…Figure 3 shows γ (T, H) plotted as a function of √ µ 0 H for T = 6, 8, 10, 12 and 14 K. Above 1 tesla the behaviour is linear, consistent with the expected phenomenology of the Volovik effect. Such behaviour has been seen in the specific heats of single-crystal Y123 28 and La 2−x Sr x CuO 4 29 , and in interlayer tunneling in Bi2212 30 . For d-wave symmetry, in the superconducting state the finite ground-state specific heat coefficient is 29 in units of mJ/g.at.K 2 , where V M is the molar volume, d the unit cell length, φ 0 the flux quantum, 0 is the antinodal amplitude of the d-wave gap, and k F the Fermi wave vector at the node along the ( π,π ) direction.…”
Section: Volovik Effectmentioning
confidence: 80%
“…Experimentally these are seen most easily from a field-dependent downturn in the inplane electrical resistivity and a diamagnetic contribution to the static susceptibility. It is not widely recognised that in overdoped Bi2212 superconducting fluctuations can also reduce the electronic density of states (DOS) at the Fermi level [50][51][52] and hence decrease the spin susceptibility and affect all other properties which depend on the DOS. Although we are not aware of an explicit theoretical treatment, in our work a decrease in the measured electronic entropy as T c is approached from above must mean that there is a decrease in the electronic DOS.…”
Section: 2mentioning
confidence: 99%